Deposit guarantee evaluation and incentives analysis in a mutual guarantee system - De Giuli, Maria Elena; Maggi, Mario Alessandro; Paris, Francesco Maria (Journal of Banking & Finance, 2009)
This paper analyzes how the deposit guarantee value affects the risk incentives in a mutual guarantee system. We liken the guarantee’s value to that of a European-style contingent claims portfolio. The main feature emerging from our model is that a mutual guarantee system would give banks an adverse incentive to increase riskiness. To mitigate this incentive, we introduce a regulatory provision modelled using a path-dependent contingent claim. By comparing the mutual guarantee system with a non-mutual one, we show that the former is less expensive, but implies higher adverse incentives for the banks, especially for undercapitalized institutions.